Mitigação de danos de Dichelops melacanthus (Dallas, 1851) (Hemiptera: pentatomidae) em milho pela adubação nitrogenada de cobertura aplicada em diferentes estágios fenológicos - Follmann, Paulo Eduardo (2019)
The objective of this study was to evaluate the recovery of maize plants to Dichelops melacanthus, infested for different periods, as a function of different times of application of nitrogen fertilization in cover. The experiments were conducted in the second crop of 2018, in two cultivation sites (Location 1: Marechal Cândido RondonPR and Location 2: Toledo-PR). The experimental design was a randomized complete block factorial scheme, for two periods of green-bellied bug infestation (three and six days) and with four seasons nitrogen application (without application of N in coverage, 100 kg ha-1 of N at stage V4, 100 kg ha-1 of N at stage V8 and 100 kg ha-1 of N divided with 50% at stage V4 and 50% at stage V8) with six repetitions, making 72 plots. After emergence (V1) individual cages were installed in ten plants and these were infested with two per cage, which were kept according to the infestation periods. The results indicated that for the planting, in both places, the flowering and number of rows variables were not influenced by the infestation periods or the application periods. The variables that showed significant response either in isolation or in the interaction between factors were stem diameter, plant height, ear insertion height, ear diameter, number of grains per row, one thousand grain weight, ear weight and yield. Application of urea on cover provided recovery from the damage caused by the green bellied bug and both applications on V4, V4/8 and V8 provided recovery responses for maize plants.